2013
DOI: 10.1007/978-94-007-6143-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Viscous-Flow Calculations for KVLCC2 in Deep and Shallow Water

Abstract: Abstract. In the SIMMAN 2008 workshop, the capability of CFD tools to predict the flow around manoeuvring ships has been investigated. It was decided to continue this effort but to extend the work to the flow around ships in shallow water. In this paper, CFD calculations for the KLVCC2 are presented. The aim of the study is to verify and validate the prediction of the influence of the water depth on the flow field and the forces and moments on the ship for a full-block hull form. An extensive numerical investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Taking into consideration that a KCS ship model is used in the current study, the calculated values of form factor exhibit a similar trend to (Toxopeus, S., 2011) in which computational fluid dynamics (CFD) were employed to calculate the viscous flow for KLVCC2 and showed that form factor varies with condition change from shallow to deep water. It is observed from Figure 25 that there exists a clearer relation between form factor (1+k) and water depth to ship model draft ratio (H/T).…”
Section: Form Factormentioning
confidence: 61%
“…Taking into consideration that a KCS ship model is used in the current study, the calculated values of form factor exhibit a similar trend to (Toxopeus, S., 2011) in which computational fluid dynamics (CFD) were employed to calculate the viscous flow for KLVCC2 and showed that form factor varies with condition change from shallow to deep water. It is observed from Figure 25 that there exists a clearer relation between form factor (1+k) and water depth to ship model draft ratio (H/T).…”
Section: Form Factormentioning
confidence: 61%
“…Thorough code verification is performed for all releases of ReFRESCO [45]. Earlier applications of ReFRESCO in the NATO context can be found in [46][47][48][49][50][51][52]. In the present simulations, a single-phase, incompressible fluid was adopted.…”
Section: Numerical Solver Boundary Conditions and Turbulence Modelsmentioning
confidence: 99%
“…Specifically, although in model-scale computations, a significant portion of the ship hull is covered by a laminar layer, most turbulence models assume the flow is fully turbulent. Yet, results with accuracy of a few percentage error can be found in the open literature [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%